The effect of Bacillus sp.(B43) on the growth of Pak choy and Red tilapia in aquaponics system - Tajul Afif, Abdullah; Mohammad Moneruzzaman, Khandaker; Salmah, Mohamed; Mohammad Hailmi, Sajili (2018)
The objective of this study is to determine the effect of Bacillus sp. (B43) which were cultured into aquaponics system to enhance the red tilapia (Oreochromis sp.) and Pak Choy (Brassica rapa) growth performance. Six aquaponics sets have been setup, three (3) for control (without the addition of Bacillus sp. (B43) culture) and another three (3) for bacteria treatment. The plant seedlings were transplanted into the aquaponics set a week after the fish were released into the tank. The experiment started by culturing the Bacillus sp. (B43) into the tank at 4x105/ml. Parameters such as fish length, fish body weight, plant height, number of leaves, ammonia content, nitrate content, pH, Dissolved Oxygen (DO), were recorded weekly. The dry weight of the plants was recorded at the end of the experiment. All the data has been analysed by using IBM SPSS Statistic version 25. Independent Sample T-test was chosen to compare the mean of every data collected by weeks. For plant height, the result showed that there are no significant differences between the control and bacteria treatment. However plant height mean for control at week fourth was 5.678 ± 1.366 g lower than bacteria treatment 5.700 ± 1.211 g. Analysis for a number of leaf and dry weight of Pak Choy also show no significant difference between bacteria treatment and control. However, the dry weight mean for control was 0.904 ± 0.355 g and for bacteria treatment is 0.947 ± 0.573 g. The fish weight and fish length showed there is no significant difference between the bacteria treatment and control. As a conclusion, the addition of Bacillus sp. (B43) at 32x106/80ml into at 190 liter aquaponics system of cultivating red tilapia (30 tails) and Pak Choy (6) does not show any significant difference in fish and plant growth as well as the water quality for ammonia and nitrate content.